INTEGRATION OF SMED AND TRIZ IN IMPROVING PRODUCTIVITY AT SEMICONDUCTOR INDUSTRY (Jurnal Mekanikal, 2018)
Rapid equipment changeover is a vital driver in enabling a ‘World Class Manufacturing’ organization besides the other core elements of continuous production flow and Lean based activities. With respect to the above statement, a case study on a test equipment changeover was conducted at Intel Technology Sdn. Bhd. The core objective of this study is to reduce the changeover duration by identifying opportunities and enhancing the overall process. Well renowned changeover techniques of SMED were integrated with the problem solving tool called TRIZ to counter problems like non standardized and non optimized practices in the current changeover process. The techniques helped to minimize, substitute or eliminate the changeover activities. Most of the solution focused mainly on task simplification and also hardware redesigning. The changeover process improvement and duration reduction helped the organization mainly in capital and cost savings with other intangible improvements especially in productivity. This case study has helped to demonstrate that though SMED and TRIZ are 2 different techniques with individual strengths and weakness but the integration of these techniques have helped to optimize the changeover process to meet the objective.
Keywords: Rapid changeover; semiconductor; test handler; SMED; TRIZ